THE SNAKES COLLECTION FROM PAPUA, INDONESIA WITH NOTES ON ANALYSIS OF STOMACH CONTENT - Keliopas Krey; Denisa Taran; Hendrik Burwos; Irvan Sidik (Jurusan Biologi, FMIPA, Universitas Papua, 2019)
A complete list of snake species found in Papua is essential for the conservation and management of these species in the future. This study provides a basic overview of the snake’s specimens deposited in the Laboratorium Zoology UNIPA (LZU) at Manokwari, West Papua Province during at last 15 years. In addition, these data are compared with specimens from the Muzeum Zoologicum Bogoriense (MZB) at Cibinong, West Java. We recorded 30 species of snakes from LZU (36.1%), and 43 species from MZB (51.8%), of the 83 species reported by Allison (2007). Clearly much more collecting effort needs to be focused on Papua, as less than 50% of the known species have voucher specimens in a museum. Of the species on collection, Morelia viridis is the only protected species on Papua, while Lycodon aulicus is the only alien species. We also conducted a through investigation of prey content for each species using preserved stomach contents. We dissected a total of 93 specimens. Twenty-nine percent of the specimens contained prey items. We discovered four categories of prey items, whole body, body parts, shell, and hair. The prey items belonged to the following four classes of animals: Reptiles (56%), Amphibians (16%), Mammals (19%), and Osteichtyes (9%).